Prevalence of Toothache and Associated Factors: A Population-Based Study in Southeast Iran - Kakoei, Shahla; Parirokh, Masoud; Nakhaee, Nouzar; Jamshidshirazi, Forogh; Rad, Maryam; Kakooei, Sina (Iranian Endodontic Journal, 2013)
Introduction: This study was carried out to estimate toothache prevalence among adult residents in Kerman. Materials and Methods: This cross-sectional, population-based study was conducted among individuals aged over 18 years (n=1800). The relevant data on the prevalence of toothache and associated factors were collected by interviewing the individuals in their homes and filling out a questionnaire designed by the examiners. Prevalence of toothache and associated factors that patients recalled previous to their interview were analyzed by chi-square test and multivariate logistic regression analysis. Results: Nine hundred ninety-one individuals (55.1%) reported toothache during the 6 months before the interview. The participants who flossed daily, had regular dental visits, and had higher education showed a significantly lower prevalence of toothache (P<0.05), whereas regular tooth brushing and economic level of residency had no significant effect on the prevalence of toothache. Individuals between the ages of 26 and 45 [odds ratio (OR)=2.0], with a family size of more than 4 (OR=1.5), not using dental floss (OR=1.5), or having a mental or psychological illness (OR=1.5) were more likely to have a history of toothache. Conclusion: High prevalence of toothache (more than half) among residents of Kerman shows a serious and major public health problem. Toothache prevalence in middle aged adults, lower education, bigger family size, lower dental hygiene habit and/or those having mental or psychological illness were more common in the city of Kerman.